2020
DOI: 10.4239/wjd.v11.i9.374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long noncoding RNA-associated competing endogenous RNA network in glucagon-like peptide-1 receptor agonist-mediated protection in β cells

Abstract: BACKGROUND Long noncoding RNAs (lncRNAs) and mRNAs are widely involved in various physiological and pathological processes. The use of glucagon-like peptide-1 receptor agonists (GLP-1RAs) is a novel therapeutic strategy that could promote insulin secretion and decrease the rate of β-cell apoptosis in type 2 diabetes mellitus (T2DM) patients. However, the specific lncRNAs and mRNAs and their functions in these processes have not been fully identified and elucidated. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Furthermore, identification of the role of these T2D-lncRNAs may provide a better understanding of the molecular network in the development of T2D. As recently reported, the treatment of glucagon-like peptide-1 receptor agonists (GLP1RAs) in the T2D cell model showed that lncRNA NONRATT027738 is in the core of the molecular networks that resulted in the β-cell improvements following the GLP1ARs treatment [ 93 ].…”
Section: Long Non-coding Rnas (Lncrnas) In Type 2 Diabetes (T2d)mentioning
confidence: 99%
“…Furthermore, identification of the role of these T2D-lncRNAs may provide a better understanding of the molecular network in the development of T2D. As recently reported, the treatment of glucagon-like peptide-1 receptor agonists (GLP1RAs) in the T2D cell model showed that lncRNA NONRATT027738 is in the core of the molecular networks that resulted in the β-cell improvements following the GLP1ARs treatment [ 93 ].…”
Section: Long Non-coding Rnas (Lncrnas) In Type 2 Diabetes (T2d)mentioning
confidence: 99%
“… 43 Geniposide inhibits the early stage of lipotoxicity-induced β-cell apoptosis, and GLP-1R plays a critical role by counteracting lipotoxicity in INS-1 pancreatic islet β cells. 44 Cui et al 45 analyzed the microarray data of INS-1 cells treated with geniposide and identified key lncRNAs and mRNAs in a 2021 study. They found that the lncRNA NONRATT027738 interacts with all three hub mRNAs ( Pomc, Htr2a , and Agtr1a ).…”
Section: Introductionmentioning
confidence: 99%